Preparation method and application of electro-Fenton composite electrode containing silicone oil
By using transition metal oxides to etch graphite felt in electro-Fenton technology to prepare cathode materials, and adding silicone oil to its pores, combined with an ion exchange membrane as a solid electrolyte, the problems of low oxygen solubility and secondary pollution of liquid electrolytes are solved. Efficient organic wastewater degradation and environmentally friendly production processes are achieved.
Patent Information
- Application Number
- CN202411799361.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-09
AI Technical Summary
When the existing electrofenton technology treats organic wastewater, the solubility of oxygen in water is low, resulting in low efficiency of hydrogen peroxide formation and organic pollutant degradation. At the same time, the use of liquid electrolytes will lead to secondary pollution and increase costs.
The transition metal oxide is engraved with an efficient cathode material at high temperature at high temperature, and silicon oil is added to its channels to improve the oxygen diffusion and hydrophobicability. At the same time, the ion exchange membrane is used as a solid electrolyte to replace the traditional liquid electrolyte.
It improves the oxygen diffusion flux and water flooding resistance of the electro-Fenton composite electrode, enhances the formation of active oxygen and the degradation efficiency of organic pollutants, eliminates secondary pollution caused by liquid electrolyte, and reduces production costs.
Smart Images

Figure CN119330468A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic wastewater treatment, and particularly relates to a preparation method and application of an electro-Fenton composite electrode containing silicone oil. Background Art
[0002] Electro-Fenton technology is an advanced technology for wastewater treatment. It relies on clean electrons to induce the generation of strong oxidative active groups, which then attack refractory organic pollutants and oxidize them into low-toxic or non-toxic small molecules. This technology is particularly suitable for treating bio-refractory organic pollutants. Electro-Fenton technology can generate hydrogen peroxide in situ and activate it into hydroxyl radicals. The process is rapid, environmentally friendly and does not require special equipment. It has good application prospects in the field of organic wastewater treatment.
[0003] At present, the cathode materials used in the electro-Fenton technology are mainly composed of carbon materials, which have the characteristics of high conductivity, good stability, low cost and environmental friendliness. However, the unmodified carbon materials lack active sites themselves, resulting in a low hydrogen peroxide yield. Therefore, the carbon materials need to be modified to improve their physical and chemical properties. Choosing carbon materials etched with transition metal oxides as cathode materials can not only increase the specific surface area of the carbon materials, make their surfaces rougher, and provide more active sites, but also promote oxygen adsorption and reactive oxygen formation, which is beneficial to the oxidative degradation of organic pollutants. Under flooding conditions, due to the low solubility of oxygen in water, it is more difficult to transport oxygen to the electrode pores through water, which is not conducive to the formation of hydrogen peroxide and the degradation of organic pollutants. When treating organic wastewater, another limiting factor of the electro-Fenton technology is that the solution needs to have a high conductivity. Generally, liquid electrolytes can be added to the water to increase the conductivity of the wastewater, but it will lead to secondary pollution and increased costs.
[0004] The present invention uses ion exchange membrane as a solid electrolyte to replace the traditional liquid electrolyte, constructs a new type of electro-Fenton technology to eliminate the secondary pollution caused by the liquid electrolyte, and is applied to the treatment of organic wastewater. Graphite felt is etched at high temperature by transition metal oxides to prepare a high-efficiency cathode material; silicone oil is added to the pores of the cathode material to increase the oxygen diffusion flux and the hydrophobicity of the catalyst pores to promote the improvement of the electrode's anti-flooding performance, which is beneficial to the formation of active oxygen and the degradation of organic pollutants. Therefore, the present invention has broad application prospects in the field of organic wastewater treatment. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing an electro-Fenton composite electrode containing silicone oil, and to apply it to the treatment of organic wastewater. The composite electrode prepared by the method has high current efficiency, low oxygen diffusion resistance, good anti-flooding performance, simple process, low cost, environmental friendliness, and easy large-scale production.
[0006] The technical solution of the present invention is: etching graphite felt at high temperature by transition metal oxides to prepare a high-efficiency cathode material, adding silicone oil, selecting an ion exchange membrane as a solid electrolyte, constructing a new electro-Fenton technology system, and applying it to treat organic wastewater.
[0007] The present invention relates to a method for preparing an electro-Fenton composite electrode containing silicone oil and application thereof, comprising the following steps:
[0008] (1) A graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and then dried; then, it was immersed in an acetate solution of a transition metal with a molar concentration of 5.0 mmol / L and ultrasonically treated for 30 min. The graphite felt was taken out and dried naturally, then placed in a muffle furnace and calcined at 300 °C for 1.0 h, and then heated to 400 °C for 1.0 h to obtain a transition metal oxide-etched graphite felt cathode material;
[0009] The transition metal acetate is any one or two of iron acetate, cobalt acetate or manganese acetate;
[0010] (2) Add silicone oil to n-hexane, wherein the mass percentage concentration of silicone oil is 2.0-10.0%, and ultrasonically treat for 10 min. Then, immerse the graphite felt etched with transition metal oxide in the above-mentioned mixture and ultrasonically treat for 30 min. Then, vacuum dry it at 80 °C for 2.0 h, and finally calcine it at 200 °C for 1.0 h to obtain an electro-Fenton composite electrode containing silicone oil.
[0011] The silicone oil is any one of dimethyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl ethoxy silicone oil, methyl vinyl silicone oil or methyl hydroxy silicone oil;
[0012] (3) The ion exchange membrane was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0013] The ion exchange membrane is any one of Nafion N324, Nafion N117 or Nafion N438;
[0014] (4) At room temperature, an electro-Fenton wastewater treatment device was assembled using an acrylic sheet as a frame, a stainless steel mesh as a current collector, an electro-Fenton composite electrode containing silicone oil as a cathode, a ruthenium-iridium-titanium plate as an anode, and an ion exchange membrane as a solid electrolyte. The organic wastewater was treated under certain current density and aeration conditions. Samples were taken at regular intervals for analysis, and the degradation rate of organic pollutants in the wastewater was calculated.
[0015] The advantages of the present invention over the prior art are mainly reflected in:
[0016] (1) The present invention selects to etch the graphite felt with transition metal oxides, so that a large number of defects and porous structures are formed on its surface, providing more active sites, which are beneficial to oxygen adsorption, active oxygen formation and oxidative degradation of organic pollutants.
[0017] (2) Adding silicone oil into the pores of graphite felt etched by transition metal oxides can increase the oxygen diffusion flux and the hydrophobicity of the catalyst pores, promote the improvement of the electrode's anti-flooding performance, and thus facilitate the formation of active oxygen and the degradation of organic pollutants.
[0018] (3) Using ion exchange membrane as solid electrolyte instead of traditional liquid electrolyte to construct a new electro-Fenton technology, eliminating the secondary pollution caused by liquid electrolyte.
[0019] (4) The composite electrode prepared by the present invention has the advantages of low cost, good cycle stability, low oxygen mass transfer resistance, no secondary pollution, simple operation and high organic wastewater degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Schematic diagram of the electro-Fenton device assembled in Example 1.
[0021] Figure 2 This is a scanning electron microscope photograph of the composite electrode prepared in Example 1. DETAILED DESCRIPTION
[0022] The specific implementation modes of the present invention are further explained below, but the scope of protection claimed by the present invention is not limited thereto. Example 1
[0023] The graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and dried; then, it was immersed in a cobalt acetate solution with a molar concentration of 5.0 mmol / L and ultrasonically treated for 30 min. The graphite felt was taken out and dried naturally, and then placed in a muffle furnace and calcined at 300 °C for 1.0 h, and then heated to 400 °C for calcination for 1.0 h to obtain a graphite felt cathode material etched with cobalt tetroxide;
[0024] Dimethyl silicone oil was added to n-hexane, wherein the mass percentage concentration of dimethyl silicone oil was 2.0%, and ultrasonic treatment was performed for 10 minutes. Then, the etched graphite felt was immersed in the above-mentioned mixed solution and ultrasonic treatment was performed for 30 minutes. Subsequently, it was vacuum dried at 80°C for 2.0 hours, and finally calcined at 200°C for 1.0 hour to obtain an electro-Fenton composite electrode containing silicone oil.
[0025] The ion exchange membrane Nafion N324 was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0026] At room temperature, an electro-Fenton wastewater treatment device was assembled with an acrylic plate as the frame, a stainless steel mesh as the current collector, an electro-Fenton composite electrode containing silicone oil with a length, width and thickness of 2.0 cm, 2.0 cm and 0.2 cm respectively as the cathode, a ruthenium-iridium-titanium plate as the anode and Nafion N324 as the solid electrolyte to treat 100 mL of 20 mg / L golden orange II dye wastewater. At a current density of 3.0 mA / cm 2 When the flow rate was 10 mL / min, the degradation rate of Golden Orange II in the wastewater was 96.6% after 90 min. Under the same experimental conditions, when the etched graphite felt without silicone oil was used as the cathode, the degradation rate of Golden Orange II in the wastewater was 86.1%. Example 2
[0027] The graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and dried; then, it was immersed in a 5.0 mmol / L ferric acetate solution and ultrasonically treated for 30 min. The taken out graphite felt was naturally dried and placed in a muffle furnace, calcined at 300 °C for 1.0 h, and then heated to 400 °C for 1.0 h to obtain an iron oxide-etched graphite felt cathode material;
[0028] Methyl hydrogenated silicone oil was added to n-hexane, wherein the mass percentage concentration of the methyl hydrogenated silicone oil was 5.0%, and ultrasonic treatment was performed for 10 minutes. Then, the etched graphite felt was immersed in the above-mentioned mixed solution and ultrasonic treatment was performed for 30 minutes. Subsequently, it was vacuum dried at 80°C for 2.0 hours, and finally calcined at 200°C for 1.0 hour to obtain an electro-Fenton composite electrode containing silicone oil.
[0029] The ion exchange membrane Nafion N324 was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0030] At room temperature, an electro-Fenton wastewater treatment device was assembled with an acrylic plate as the frame, a stainless steel mesh as the current collector, an electro-Fenton composite electrode containing silicone oil with a length, width and thickness of 2.0 cm, 2.0 cm and 0.2 cm respectively as the cathode, a ruthenium-iridium-titanium plate as the anode and Nafion N324 as the solid electrolyte to treat 100 mL of 20 mg / L golden orange II dye wastewater. At a current density of 3.0 mA / cm 2 When the flow rate was 10 mL / min, the degradation rate of Golden Orange II in the wastewater was 88.5% after 90 min. Under the same experimental conditions, when the etched graphite felt without silicone oil was used as the cathode, the degradation rate of Golden Orange II in the wastewater was 83.7%. Example 3
[0031] The graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and dried; then, it was immersed in a cobalt acetate solution with a molar concentration of 5.0 mmol / L and ultrasonically treated for 30 min. The graphite felt was taken out and dried naturally, and then placed in a muffle furnace and calcined at 300 °C for 1.0 h, and then heated to 400 °C for calcination for 1.0 h to obtain a graphite felt cathode material etched with cobalt tetroxide;
[0032] Methylphenyl silicone oil was added to n-hexane, wherein the mass percentage concentration of methylphenyl silicone oil was 2.0%, and ultrasonic treatment was performed for 10 minutes. Then, the etched graphite felt was immersed in the above-mentioned mixed solution and ultrasonic treatment was performed for 30 minutes. Subsequently, it was vacuum dried at 80°C for 2.0 hours, and finally calcined at 200°C for 1.0 hour to obtain an electro-Fenton composite electrode containing silicone oil.
[0033] The ion exchange membrane Nafion N324 was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0034] At room temperature, an electro-Fenton wastewater treatment device was assembled with an acrylic plate as the frame, a stainless steel mesh as the current collector, an electro-Fenton composite electrode containing silicone oil with a length, width and thickness of 2.0 cm, 2.0 cm and 0.2 cm respectively as the cathode, a ruthenium-iridium-titanium plate as the anode and Nafion N324 as the solid electrolyte to treat 100 mL of 20 mg / L golden orange II dye wastewater. At a current density of 3.0 mA / cm 2 When the flow rate was 10 mL / min, the degradation rate of Golden Orange II in the wastewater was 93.3% after 90 min. Under the same experimental conditions, when the etched graphite felt without silicone oil was used as the cathode, the degradation rate of Golden Orange II in the wastewater was 86.1%. Example 4
[0035] The graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and dried; then, it was immersed in a mixed solution of 5.0 mmol / L cobalt acetate and 5.0 mmol / L manganese acetate, and ultrasonically treated for 30 min. The taken out graphite felt was naturally dried and placed in a muffle furnace, calcined at 300 °C for 1.0 h, and then heated to 400 °C for 1.0 h to obtain a graphite felt cathode material etched with cobalt tetroxide and manganese dioxide;
[0036] Methylethoxy silicone oil was added to n-hexane, wherein the mass percentage concentration of methylethoxy silicone oil was 10.0%, and ultrasonic treatment was performed for 10 minutes. Then, the etched graphite felt was immersed in the above-mentioned mixed solution and ultrasonic treatment was performed for 30 minutes. Subsequently, it was vacuum dried at 80°C for 2.0 hours, and finally calcined at 200°C for 1.0 hour to obtain an electro-Fenton composite electrode containing silicone oil.
[0037] The ion exchange membrane Nafion N117 was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0038] At room temperature, an electro-Fenton wastewater treatment device was assembled with an acrylic plate as the frame, a stainless steel mesh as the current collector, an electro-Fenton composite electrode containing silicone oil with a length, width and thickness of 2.0 cm, 2.0 cm and 0.2 cm respectively as the cathode, a ruthenium-iridium-titanium plate as the anode and Nafion N117 as the solid electrolyte to treat 100 mL of 20 mg / L golden orange II dye wastewater. The current density was 3.0 mA / cm 2 When the flow rate was 10 mL / min, the degradation rate of Golden Orange II in the wastewater was 85.4% after 90 min. Under the same experimental conditions, when the etched graphite felt without silicone oil was used as the cathode, the degradation rate of Golden Orange II in the wastewater was 88.2%. Example 5
[0039] The graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and dried; then, it was immersed in a cobalt acetate solution with a molar concentration of 5.0 mmol / L and ultrasonically treated for 30 min. The graphite felt was taken out and dried naturally, and then placed in a muffle furnace and calcined at 300 °C for 1.0 h, and then heated to 400 °C for calcination for 1.0 h to obtain a graphite felt cathode material etched with cobalt tetroxide;
[0040] Methyl vinyl silicone oil was added to n-hexane, wherein the mass percentage concentration of methyl vinyl silicone oil was 2.0%, and ultrasonic treatment was performed for 10 minutes. Then, the etched graphite felt was immersed in the above-mentioned mixed solution and ultrasonic treatment was performed for 30 minutes. Subsequently, it was vacuum dried at 80°C for 2.0 hours, and finally calcined at 200°C for 1.0 hour to obtain an electro-Fenton composite electrode containing silicone oil.
[0041] The ion exchange membrane Nafion N438 was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0042] At room temperature, an electro-Fenton wastewater treatment device was assembled with an acrylic plate as the frame, a stainless steel mesh as the current collector, an electro-Fenton composite electrode containing silicone oil with a length, width and thickness of 2.0 cm, 2.0 cm and 0.2 cm respectively as the cathode, a ruthenium-iridium-titanium plate as the anode and Nafion N438 as the solid electrolyte to treat 100 mL of 20 mg / L golden orange II dye wastewater. The current density was 3.0 mA / cm 2 When the flow rate was 10 mL / min, the degradation rate of Golden Orange II in the wastewater was 92.5% after 90 min. Under the same experimental conditions, when the etched graphite felt without silicone oil was used as the cathode, the degradation rate of Golden Orange II in the wastewater was 85.4%. Example 6
[0043] The graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and then dried; then, it was immersed in a manganese acetate solution with a molar concentration of 5.0 mmol / L and ultrasonically treated for 30 min. The taken out graphite felt was naturally dried and placed in a muffle furnace, calcined at 300 °C for 1.0 h, and then heated to 400 °C for 1.0 h to obtain a graphite felt cathode material etched with manganese dioxide;
[0044] Methylhydroxy silicone oil was added to n-hexane, wherein the mass percentage concentration of methylhydroxy silicone oil was 2.0%, and ultrasonic treatment was performed for 10 minutes. Then, the etched graphite felt was immersed in the above-mentioned mixed solution and ultrasonic treatment was performed for 30 minutes. Subsequently, it was vacuum dried at 80°C for 2.0 hours, and finally calcined at 200°C for 1.0 hour to obtain an electro-Fenton composite electrode containing silicone oil.
[0045] The ion exchange membrane Nafion N324 was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h.
[0046] At room temperature, an electro-Fenton wastewater treatment device was assembled with an acrylic plate as the frame, a stainless steel mesh as the current collector, an electro-Fenton composite electrode containing silicone oil with a length, width and thickness of 2.0 cm, 2.0 cm and 0.2 cm respectively as the cathode, a ruthenium-iridium-titanium plate as the anode and Nafion N324 as the solid electrolyte to treat 100 mL of 20 mg / L golden orange II dye wastewater. At a current density of 3.0 mA / cm 2 When the flow rate was 10 mL / min, the degradation rate of Golden Orange II in the wastewater was 90.1% after 90 min. Under the same experimental conditions, when the etched graphite felt without silicone oil was used as the cathode, the degradation rate of Golden Orange II in the wastewater was 84.6%.
Claims
1. A method for preparing an electro-Fenton composite electrode containing silicone oil, characterized in that: Follow the steps below, (1) A graphite felt with a thickness of 0.2 cm was washed with ethanol and deionized water respectively, and then dried; then, it was immersed in an acetate solution of a transition metal with a molar concentration of 5.0 mmol / L and ultrasonically treated for 30 min. The graphite felt was taken out and dried naturally, then placed in a muffle furnace, calcined at 300 °C for 1.0 h, and then heated to 400 °C for 1.0 h to obtain a transition metal oxide-etched graphite felt cathode material; (2) Add silicone oil to n-hexane, wherein the mass ratio concentration of silicone oil is 2.0-10.0%, and ultrasonically treat for 10 min. Then, immerse the graphite felt etched with transition metal oxide in the above-mentioned mixture and ultrasonically treat for 30 min. Then, vacuum dry it at 80 °C for 2.0 h, and finally calcine it at 200 °C for 1.0 h to obtain an electro-Fenton composite electrode containing silicone oil. (3) The ion exchange membrane was immersed in a 5.0% hydrogen peroxide solution and treated at 80 °C for 1.0 h. After washing with deionized water, the membrane was placed in a 0.5 mol / L sulfuric acid solution and treated at 80 °C for 2.0 h. Finally, the membrane was placed in deionized water and treated at 80 °C for 2.0 h. The transition metal acetate in step (1) is any one or two of ferric acetate, cobalt acetate or manganese acetate; The silicone oil in step (2) is any one of dimethyl silicone oil, methyl hydrogen silicone oil, methyl phenyl silicone oil, methyl ethoxy silicone oil, methyl vinyl silicone oil or methyl hydroxy silicone oil; The ion exchange membrane in step (3) is any one of Nafion N324, Nafion N117 or Nafion N438.
2. The application of an electro-Fenton composite electrode containing silicone oil obtained by the method according to claim 1, characterized in that: At room temperature, an electro-Fenton wastewater treatment device was assembled with acrylic sheet as frame, stainless steel mesh as current collector, electro-Fenton composite electrode containing silicone oil as cathode, ruthenium-iridium-titanium plate as anode, and ion exchange membrane as solid electrolyte. Organic wastewater was treated under certain current density and aeration conditions. Samples were taken for analysis at regular intervals, and the degradation rate of organic pollutants in the wastewater was calculated.
Citation Information
Patent Citations
An apparatus for conducting an electro-fenton reaction for decomposing organic chemical compounds
CN106660837A
Lithium supplement additive for lithium ion cathode material and preparation method thereof
CN112490415A
Graphite felt loaded two-dimensional layered nanosheet electro-Fenton cathode material as well as preparation method and application thereof
CN112811536A
Preparation method and use of graphite felt (GF)-supported metal-organic framework (MOF) cathode material
US20210309681A1